Wpływ antropopresji na zmienność stanów wody jeziora Wierzchowo w latach 1976-2009 = Anthropogenic impact on water level fluctuations in lake Wierzchowo in the years 1976-2009 - Ptak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents water level fluctuations in lake Wierzchowo. Hydraulic engineering structures were the main element determining their course. Withdrawal from the damming of this lake significantly changed the circumstances related to water level fluctuations. In the light of the implemented program, designed to increase the Polish water resources, this situation can be regarded as exceptional.
Keywords: jeziora; wahania stanów wody; zasoby wodne; lakes; water level; water resources